Everyday Da'wah in a Secular Campus: Muslim Students and Informal Islamic Communication at Andhra University - Eki Arum Khasanah; Nesya Setyarini; Anil Kunta (Fakultas Dakwah dan Komunikasi UIN Sunan Kalijaga, 2024)
This paper explores the everyday practices of informal Islamic communication among Muslim students at Andhra University, a public university in secular India. The study investigates how da'wah is embodied in daily interactions, lifestyle choices, and peer engagement beyond traditional religious settings. Employing a qualitative approach through in-depth interviews and participant observation, this research uncovers how Muslim youth navigate their religious identity and communicate Islamic values within a multicultural academic environment. The findings reveal that everyday da'wah takes subtle forms—such as reminding friends to pray, sharing Islamic content on social media, or demonstrating ethical behavior—as a means of religious expression and social connection. This paper contributes to the discourse on Islamic communication by highlighting the significance of non-institutional da'wah in pluralistic and secular spaces like Indian universities.